Sustaining dignity? Food insecurity in homeless young people in urban Australia. (18th August 2014) - Crawford, Belinda; Yamazaki, Rowena; Franke, Elise; Amanatidis, Sue; Ravulo, Jioji; Steinbeck, Kate; Ritchie, Jan; Torvaldsen, Siranda
Abstract : Issue addressed: Food insecurity is recognised as an increasing problem in disadvantaged and marginalised groups. The aim of this study was to investigate issues associated with food insecurity and nutrition in young people experiencing, or at risk of, homelessness in metropolitan Australia. Methods: Eight focus group discussions were conducted with 48 young people (aged between 15 and 25 years) in specialist homelessness services in central and south‐western Sydney. Results: Participants described daily experiences of food insecurity, persistent hunger and poverty. Structural barriers to food security and nutrition were identified and included poverty and reduced physical access to fresh foods. Participants also described a desire to save time, for convenience and to be socially connected. Despite the hardships and the chaos of youth homelessness, the groups were defined by their strength of character, resilience and hope for the future. Conclusion: Homeless young people within central and south‐western Sydney report varying degrees of food insecurity, despite being supported by specialist youth homelessness services. So what?: A collaborative, multistrategic approach with youth participation is required to further enhance the capacity of youth services to improve food security, food access and the availability of nutritious foods for homeless young people. A greater focus on advocacy and policy action is also required to bring food security and nutrition to the forefront of national efforts to improve the health and welfare of disadvantaged groups. Abstract : Focus group discussions were conducted with homeless young people experiencing, or at risk of, homelessness. Despite the support of specialist youth homelessness services, participants reported varying degrees of food insecurity. Barriers to food security and nutrition included poverty, reduced access to fresh foods and a desire for convenience.